Stent Conformity in Curved Vascular Models with Simulated Aneurysm Necks Using Flat-Panel CT: An In Vitro Study - Ebrahimi, N.; Claus, B.; Lee, C.-Y.; Biondi, A.; Benndorf, G. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Radiographic visibility of self-expandable intracranial stents is insufficient for assessment of conformability and deployment characteristics. The purpose of this study was to evaluate stent mechanics in a curved vessel model by using Flat-Panel CT (FPCT).MATERIALS AND METHODS: The following stents were used: Neuroform 2, Neuroform Treo, Enterprise, and LEO. All stents were bent in the same polytetrafluoroethylene tubes with various angles ranging from 150° to 30°. To visualize potential prolapse of the stent struts, 4-, 5-, and 8-mm openings were created. FPCTs were obtained using a C-arm with flat detector.RESULTS: FPCT scans provided excellent visualization of deployment characteristics and stent mechanics and was superior to digital subtraction angiography (DSA) and digital radiography (DR). The Neuroform2/Treo showed, with increasing angle and diameter of the opening, a continuous increase in cell size. These stents also showed an outward prolapse at the convexity and an inwards prolapse of struts at the concavity of the curvature. The Enterprise showed an increasing trend to flatten and to kink with curvatures that are more acute. The LEO showed fewer trends to kink but an inward crimping of its ends with more acute angles.CONCLUSIONS: Deployment characteristics and conformability to a curved vessel model vary considerably, depending on the angle and the stent design. Adverse mechanics such as increased cell opening, strut prolapse, flattening, and kinking occur during stent placement in a curved vessel model, and may gain clinical importance. FPCT is superior to DSA and DR in visualizing small metallic stents and enables accurate detection of adverse stent mechanics.